Inovação e dinâmica organizacional: novas perspectivas em recursos humanos estudo com organizações na Serra do Cipó MG - Glauciene Silva Martins (2018)
This thesis describes and analyzes the phenomenon of innovation in the context of Serra do Cipó, Minas Gerais, based on elements of organizational dynamics and its articulation with the human resources dimension. Using a theoretical framework on innovation, social innovation and resource-based vision, considering the studies in the field of human resource management and organizational dynamics, a qualitative empirical study was adopted as a methodological strategy in the tourism sector of the chosen region. Data collection consisted initially of a preliminary research about the tourism experience. Participant observations and semistructured field interviews were also used with actors directly related to the local logic. The results obtained indicate the diversity of experiences, world visions and training of human resources, together with the definition of management processes and leadership; the intrinsic motivation of the individual and the commitment; the cooperation or collaboration between actors from the associativism or the construction of spaces for interaction (councils, public meetings of collective interests). Entrepreneurship and the notion of sustainability associated with it contemplated, basically, the new perspectives in human resources found, opening possibilities for the advancement of research towards the development of social technologies